Pengenalan Konsep Keuangan Sederhana Pada Usaha Mikro Informal Noken Di Distrik Abepura - Muslimin, Ulfah Rizky; Tandililing, Elia Madatu (The Community Engagement Journal, 2023)
This activity service focuses on Jayapura City, especially Abepura District with the purpose of providing an introduction to simple financial concepts for Noken entrepreneurs in Abepura District. This activity aimed at native Papuan women entrepreneurs who sell noken, one of Papua's traditional crafts, made from plants, taken from tree bark and woven into bags that are used as places to store goods. There are 10 womens (Papuan mothers) that became seller in Abepura District were given training through the interview method regarding the initial understanding of noken sellers, the obstacles they face if any, then continued with an introduction to simple financial concepts related to the business they’ve run. The output of this service activity is to provide an introduction to simple financial concepts so as to increase understanding regarding financial management for informal noken micro businesses in Abepura District. Furthermore, it is hoped in the future they will be able to record and manage their own finances in more detail and orderly. Keywords: Financial, Micro Informal, Noken